External Performance in Low-Income Countries - Prati, Alessandro (International Monetary Fund, 2011)
Assessments of exchange rate misalignments and external imbalances for low-income countries are challenging because methodologies developed for advanced and emerging economies cannot be automatically applied to poorer nations. This paper uses a large database, unique in the set of indicators and number of countries it covers, to estimate the relationship in low-income countries between a set of fundamentals in the medium to long term and the real effective exchange rate, the current account, and the net external assets position